Synchronous adenocarcinoma of caecum, transverse colon and jejunum - Leong, Benjamin Dak Keung; Ramu, P.; Kumar, V.M.; Chuah, J.A. (Malaysian Medical Association, 2008)
Synchronous cancers are defined as malignant tumours that occur simultaneously, each of which must be distinct with no possibility of one being the metastasis of the other. A 65 year old gentleman presented to us with two month history of epigastric pain associated with anaemia, loss of appetite and weight. He has no history of malignancy in his family. Colonoscopy revealed tumours at transverse colon and caecum. Intra-operatively, tumours were sited at caecum, transverse colon and jejunum. Tumours were diagnosed as synchronous adenocarcinoma histopathologically with loss of expression of MLH1 and MSH2. From literature search, this is the first reported triple synchronous tumours of the caecum, transverse colon and jejunum. We believe that this gentleman developed triple synchronous tumour through the sporadic MSI pathway.